2021
DOI: 10.3390/met11091392
|View full text |Cite
|
Sign up to set email alerts
|

Study of Coatings Formed on Zirconium Alloy by Plasma Electrolytic Oxidation in Electrolyte with Submicron Yttria Powder Additives

Abstract: Coatings with thickness 40 to 150 μm were formed by plasma electrolytic oxidation (PEO) on the zirconium alloy Zr-1Nb (Zr-1% Nb) in the slurry electrolyte containing 9 g/L Na2SiO3 5H2O, 5 g/L Na(PH2O2) and 6 g/L submicron Y2O3 yttria powder during 60 min under the AC electrical mode at current densities 20; 30 and 40 A/dm2. The surface morphology, structure, composition, and corrosion-protective ability of the formed coatings have been analyzed. At PEO current density 30 A/dm2, a predominantly tetragonal phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Thus, the trend in the Rct of the samples was: uncoated TiAl (49.6 kΩ m 2 ) < 400 V (280.1 kΩ m 2 ) < 450 V (380.2 kΩ m 2 ) < 500 V (456.7 kΩ m 2 ). In this regard, some researchers [80][81][82][83][84][85][86][87][88][89][90][91] have suggested that the substantial corrosion resistance in PEO coatings stems from the thickness of the oxide layer. Therefore, as the voltage rose, a thicker PEO film formed, which causes the penetration rate of the corrosive solution into the substrate to decrease; hence the chemical reactions culminating in the coating formation deaccelerated kinetically and thermodynamically.…”
Section: Electrochemical Impedance Spectroscopy (Eis)mentioning
confidence: 99%
“…Thus, the trend in the Rct of the samples was: uncoated TiAl (49.6 kΩ m 2 ) < 400 V (280.1 kΩ m 2 ) < 450 V (380.2 kΩ m 2 ) < 500 V (456.7 kΩ m 2 ). In this regard, some researchers [80][81][82][83][84][85][86][87][88][89][90][91] have suggested that the substantial corrosion resistance in PEO coatings stems from the thickness of the oxide layer. Therefore, as the voltage rose, a thicker PEO film formed, which causes the penetration rate of the corrosive solution into the substrate to decrease; hence the chemical reactions culminating in the coating formation deaccelerated kinetically and thermodynamically.…”
Section: Electrochemical Impedance Spectroscopy (Eis)mentioning
confidence: 99%